Territorial governance across borders. The example of the Greater Region - Caesar, Beate; Blaser, Benjamin; Pallagst, Karina (Handbook of Territorial Governance, 2025)
Keywords: Governance; Grenzüberschreitende Kooperation; Großregion (Körperschaft)

Introduction. Cross-Border Inequalities. An Exploration in the Greater Region - Connor, Ulla; Aubry, Lola (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Wohnen; Wohnungsmarkt

Grenzüberschreitende Ungleichheiten in der Großregion. Perspektiven und Daten - Himbert, Alexa (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „Seit über 20 Jahren sammelt und analysiert die Interregionale Arbeitsmarktbeobachtungsstelle (IBA·OIE) im Auftrag der politischen Verantwortlichen der Großregion vergleichbare und interpretierbare Daten über den Arbeitsmarkt auf dem Gebiet der Großregion und liefert damit die Grundlage für struktur- und arbeitsmarktpolitische Entscheidungen in der Großregion. Durch die lange und kontinuierliche Beobachtung gelingt es, ein deutliches Bild der Pendlerbewegungen und ihrer Profile im Kooperationsraum der Großregion zu zeichnen und diese engen Verflechtungen sichtbar zu machen. Allerdings werden auch die Unterschiede deutlich, die kulturell bedingt, aber auch durch die heterogenen Wirtschaftsstrukturen der Teilregionen gewachsen sind. Als Grundlage dienen zunächst die Daten der europäischen Statistikbehörde Eurostat, die in harmonisierter Form vorliegen und dadurch im grenzüberschreitenden Kontext leicht vergleichbar sind. Für die detaillierteren Indikatoren auf der Ebene der Großregion werden zudem die Daten der jeweiligen statistischen Ämter und anderer Datenproduzenten aus den Teilregionen herangezogen. Aufgrund unterschiedlicher Hintergründe und Erhebungsmethoden bedürfen die Zahlen einer deutlichen Kontextualisierung und meist einer Harmonisierung. Insbesondere die Daten zu den Grenzgängerströmen stammen aus unterschiedlichen Datenquellen, die einer Harmonisierung auf großregionaler Ebene bedürfen.“
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Vivre au sein de l’espace frontalier franco-luxembourgeois du Moyen Âge à nos jours. Nouveaux éclairages sur les interactions entre pouvoirs et pratiques. Introduction au dossier - Kaci, Maxime; Venken, Machteld; Brüll, Christoph; Kmec, Sonja (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)

Les travailleurs frontaliers atypiques face aux inégalités transfrontalières. Éclairages et défis - Mezaroş, Mădălina; Uyttebrouck, Constance; Górczyńska-Angiulli, Magdalena; Paccoud, Antoine (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article explores the dynamics of atypical cross-border workers in the Greater Region, that is to say, those who reside in a neighbouring country while maintaining employment in Luxembourg. Before highlighting the housing access inequalities that this residential dynamic entails, the analysis examines housing policies in Belgium, France, Germany and Luxembourg to better understand the disparities that intensify pressure on regional housing markets. Recent and historical data on the profiles of atypical cross-border workers are presented, along with testimonies from former residents of Luxembourg who have left the country. The study sheds light on how border housing markets respond to this growing demand, sometimes to the detriment of long-standing residents. It concludes by emphasising the need for a cross-border housing observatory to co-ordinate data collection and assess emerging inequalities, including land pressures and residential exclusion in border areas, calling for more harmonised governance to address these challenges.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Wohnen; Wohnungsmarkt

Le travail frontalier au sein de la Grande Région à l’épreuve des frontières depuis les années 1960 - Pigeron-Piroth, Isabelle; Belkacem, Rachid (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „Within the European Union, the Greater Region Saar-Lor-Lux is the region most impacted by cross-border work. Luxembourg is attracting an increasing number of workers from neighboring countries, mainly from France. This article examines how the practice of cross-border work has evolved over the last sixty years and what the territorial issues are. Rarely taken into account over a long period, the historical dimension is indeed necessary to understand the roots of the phenomenon, its structuring and diversification. The degree of permeability of borders and the reasons for crossing them have changed over time. This analysis provides an overview of cross-border work, focusing on Luxembourg as the main country of employment and Lorraine as the main place of residence for cross-border workers. Contextual factors and different processes - historical, economic, social and political - are important and have encouraged the development of cross-border work in the Greater Region: they have contributed to its institutionalization and to the structuring of the phenomenon. Finally, borders are questioned in the light of emerging territorial challenges, such as labour shortages, the ageing of the population and the resulting tensions pertaining to cross-border work.“
Keywords: Grenzarbeitnehmer

Marché du travail transfrontalier. Différentiels et interdépendances - Pigeron-Piroth, Isabelle; Schiel, Kerry (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „With its 267,300 cross-border workers in 2022, the Greater Region of SaarLorLux is often presented as a model of European integration. Borders are becoming less and less perceptible, and are disappearing for commuters travelling from one country to another. However, the Covid-19 pandemic has shown the reappearance of borders that were thought to have been forgotten. It has to be said that many border-related issues have come to the fore in recent years, all the more so because of the many challenges and tensions as well as the growing number of cross-border workers. The question of inequalities is central in this context of a cross-border labour market with strongly interwoven components.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Schicksal(e) der Großregion = Destin(s) de la Grande Région - Arbeitsgruppe Kultur der Großregion (Nomos, 2024)
Keywords: Grenzüberschreitende Kooperation; Großregion (Körperschaft)

Cross-border residential mobility of people working in Luxembourg. Developments and impacts - Nienaber, Birte; Pigeron-Piroth, Isabelle (European Borderlands. Living with Barriers and Bridges, 2017)
Keywords: Grenzarbeitnehmer; Sozialraum

Grenzüberschreitende Arbeitsmarktpolitik. Institutionen und institutionelle Steuerung des Arbeitsmarktes in der Großregion SaarLorLux-Rheinland-Pfalz-Wallonien - Albrecht, Maria; Meyer, Wolfgang (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux - Meyer, Jürgen; Rampeltshammer, Luitpold (Universaar, 2012)
Inhaltsverzeichnis: https://d-nb.info/1026984491/04
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Lebenslanges Lernen in der Großregion. Grenzenlose Weiterbildung für Pflegekräfte? - Schäfer, Désirée; Renaud, Dagmar; Riemer-Hommel, Petra (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Altenpflege; Arbeitsmarkt; Berufsbildung; Bildungswesen; Grenzarbeitnehmer; Internationale Mobilität; Krankenpflege

Die grenzüberschreitende Wohnmobilität zwischen Luxemburg und seinen Nachbarregionen - Carpentier, Samuel (Éd. Saint Paul, 2010)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage/2012/06/19/file_74/4548254.pdf
Keywords: Grenzarbeitnehmer; Pendler

Luxembourg et Grande Région. Avis de recherches [Actes des séminaires organisés par la Maison des Sciences de l'Homme Lorraine en 2008 et 2009] - Crenn, Gaëlle; Deshayes, Jean-Luc; Kmec, Sonja (Presses Universitaires de Nancy, 2010)
Aus dem Inhaltstext: „La construction des territoires en Europe" est un ouvrage issu des séminaires organisés par la Maison des Sciences de l'Homme Lorraine en collaboration avec l'Université de Luxembourg, en 2008 et 2009. L'essentiel des contributions concerne un espace transfrontalier de coopération territoriale appelé Grande Région qui regroupe des entités de quatre Étals: le Grand Duché de Luxembourg, la Wallonie et les Communauté française et germanophone en Belgique, la Lorraine en France et les 1änder de Sarre et de Rhénanie-Palatinat en Allemagne. L'événement "Luxembourg et Grande Région, capitale européenne de la culture 2007" en est une des manifestations emblématiques. Les travaux présentés permettent, non seulement de faire un état des lieux des recherches sur la Grande Région, mais aussi de s'interroger sur les raisons du développement de cet objet privilégié. Dans une perspective multidisciplinaire, ils interrogent les fondements historiques et stratégiques de la construction de l'objet Grande Région, questionnent la validité de cette échelle territoriale privilégiée de l'action publique, observent les incidences de la mobilisation de la Grande Région dans un événement culturel visant à renforcer son existence dans l'esprit des populations. Si l'approche constructiviste est dominante dans les études et permet ainsi de dénaturaliser l'objet. cette posture de recherche est cependant soumise à un examen critique. En quoi les chercheurs contribuent-ils à faire exister l'objet sur lequel ils travaillent? Comment, dans un contexte de politiques culturelles territorialisées, est-il possible de mener des études de réception indépendantes? Et quelle est, en définitive, la pertinence du concept de territoire souvent posé comme une évidence dans le langage des instances européennes? Ces approches croisées de l'entité transfrontalière Grande Région, de ses modes d'existence et de ses formes de mobilisation dans les pratiques des acteurs publics, contribuent ainsi à enrichir l'analyse des nouvelles constructions territoriales aujourd'hui à l'oeuvre, depuis l'échelle locale jusqu'à l'Europe.“
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2013/12/27/file_31/5428833.pdf
Keywords: Grenzüberschreitende Kooperation; Regionalplanung; Saar-Lor-Lux

Figures de la marginalité. Internationalisation et renationalisation d'une mémoire frontalière dans les relations du Luxembourg avec ses régions limitrophes. 1979–2007 - Bergami, Carol (Dépasser le cadre national des „lieux de mémoire“. Innovations méthodologiques, approches comparatives, lectures transnationales = Nationale Erinnerungsorte hinterfragt. Methodologische Innovationen, vergleichende Annäherungen, transnationale Lektüren, 2009)
Keywords: Kollektives Gedächtnis

Hoheitsrechte und Besitzungen Karls V. im Rheinland. Von der Mosel bis zur Nordsee. Eine Beschreibung der östlichen Grenze der Erbniederlande - Vilar Sánchez, Juan Antonio (Karl V. 1500–1558. Neue Perspektiven seiner Herrschaft in Europa und Übersee, 2002)
Keywords: Herrschaft; Karl V. (Heiliges Römisches Reich; Kaiser) (1500–1558); Rheinland

La frontière. Conception et réalités plurielles - Moreau de Gerbehaye, Claude de (Héritages culturels dans la Grande Région. Saar-Lor-Lux-Rhénanie-Palatinat., 1996)